Baeyer-Villiger Monooxygenases EthA and MymA Are Required for Activation of Replicating and Non-replicating Mycobacterium tuberculosis Inhibitors. Issue 6 (23rd June 2016) - Grant, Sarah Schmidt; Wellington, Samantha; Kawate, Tomohiko; Desjardins, Christopher A.; Silvis, Melanie R.; Wivagg, Carl; Thompson, Matthew; Gordon, Katherine; Kazyanskaya, Edward; Nietupski, Raymond; Haseley, Nathan; Iwase, Noriaki; et al.
Summary: Successful treatment of Mycobacterium tuberculosis infection typically requires a complex regimen administered over at least 6 months. Interestingly, many of the antibiotics used to treat M. tuberculosis are prodrugs that require intracellular activation. Here, we describe three small molecules, active against both replicating and non-replicating M. tuberculosis, that require activation by Baeyer-Villiger monooxygenases (BVMOs). Two molecules require BVMO EthA (Rv3854c) for activation and the third molecule requires the BVMO MymA (Rv3083). While EthA is known to activate the antitubercular drug ethionamide, this is the first description of MymA as an activating enzyme of a prodrug. Furthermore, we found that MymA also plays a role in activating ethionamide, with loss of MymA function resulting in ethionamide-resistant M. tuberculosis . These findings suggest overlap in function and specificity of the BVMOs in M. tuberculosis . Graphical Abstract: Highlights: Three novel inhibitors of non-replicating M. tuberculosis are characterized Two inhibitors require activation by EthA, a Baeyer-Villiger monooxygenase (BVMO) One inhibitor requires activation by the BVMO MymA, a novel activating enzyme Loss of MymA function confers ethionamide resistance, suggesting overlap with EthA Abstract : Grant et al. describe three novel small molecules, active against Mycobacterium tuberculosis, that require activation by the BVMOs EthA or MymA for activity. Loss of MymA function also confers resistance to ethionamide, thereby representing a novel mechanism of ethionamide resistance.